Low-P/High-T pre-Alpine metamorphism and medium-P Alpine overprint of the pelagonian zone documented in high-alumina metapelites from the Vernon massif, Western Macedonia, Northern Greece - MPOSKOS, E.; KOSTOPOULOS, D. K.; KROHE, A. (Bulletin of the Geological Society of Greece, 2001)
A low-P / high-T metamorphic event (andalusite-sillimanite series) of pre-Alpine age, identified here for the first time, has affected the metapelitic rocks of the Vernon Massif. P-T conditions of metamorphism in the western part of the Massif are estimated at -2.5 kb / 600-610°C, while in the northeastern part they are estimated to have exceeded 4.5 kb / 640°C respectively. Such P-T conditions correspond to geothermal gradients of 68°C/ km and 40°C/km for the western and the northeastern parts of the Massif respectively. The inferred steep geothermal gradients require transport of heat from deeper to shallower levels within the crust, achieved via magmatic intrusions in a continental magmatic arc setting. Alpine overprinting is characterized by P-T metamorphic conditions of ~6 kb / <350°C in the western part and ~9 kb / <570°C in the northeastern part of the Massif respectively. Low-P / high-T metamorphic rocks, occurring as klippen in the Cyclades and as blocks in the ophiolitic milanges of Crete, are interpreted as remnants of the pre-Alpine Pelagonian nappe similar to those occurring in the Vernon Massif.